The relationship between explosive power of arms and the accuracy of chest pass in basketball on the wheelchair in Erbil City - Bahjat, Nisreen (Journal of Physical Education, 2015)
The study has divided into 5 five chapters, which included the introduction and the importance of the study as it its embodied in showing the importance of the game and give more attention to those players when they need more support (special needs players).the argument of the study was ;there was a lots of unsuccessful chest pass among players and if used as it would be more achievement if performed with power and speed as well as accuracy. Therefore, the researcher has conducted the reason of uncompleted chest pass due to the lack of explosive power of the players arms which causing the unsuccessful performance. The argument of the study is to answer this question, does the uncompleted chest pass among the players due to the lack of explosive power of the arms? or there are other reasons? In other words, is there a relationship between explosive power and speed, accuracy of the chest pass of basketball players on the wheelchair? The purpose of the study was, to discover the relationship between the variables that mentioned earlier. For Para Olympics team of Kurdistan in Erbil City. In order to test the hypotheses. the researchers has assumed that ,there is a significant differences correlation between the explosive power of arms and the speed, accuracy of chest pass of basketball players on the wheelchair of Para Olympic team of Kurdistan in Kurdistan in Erbil city. The second chapter of the study contained the literature reviews which included the following, the type of strength and speed, as well as the selected skills that related to the study in Basketball. Chapter three was devoted for the research method which was the descriptive method. the sample of the study was selected deliberately. Fifteen players has selected of the para-Olympic Kurdistan team in Erbil. the tests has been selected on the basketball experts, those tests were nominated by them on the base of (75%) acceptance of the selected tests. The pilot study was applied on 8 eight players in all classification of medical aspects that categorized from (1, 5, 4). Then the main study was applied on 15 players of the sample which represents 100%.after that spss was used for statistical procedures which included the mean. Chapter four was devoted to the results and discussion which showed in tables. (Mean, SD, Correlation) of the score of pushing the heavy ball and the test of speed, accuracy of chest ball. The final chapter (chapter five), was devoted to the conclusions and recommendation -there is a significant relationship between explosive power and speed- accuracy in chest pass. And according to the research results, the researcher has recommended: The necessary of developing of explosive power of arms and conduct researches about the relationship between fitness and basic skills of basketball on the wheel chair normal people. as similar to healthy